Parental Perspectives on the Excellence of Computer Learning Media in Early Childhood Education - Taufik, Ali; Apendi, Tatang; Saidi, Suid; Istiarsono, Zen (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The introduction of basic computer media for early childhood is very important because it is one of the skills that children need in this century. Need to support parents and teachers in developing the implementation of the use of computer technology at home or at school. This study aims to determine and understand the state of learning conducted based on technology. This research uses a qualitative approach with a case study model. This study involved 15 children and 5 parents. Data obtained through interviews (children and parents) and questionnaires for parents. The results showed that children who were introduced to and taught basic computers earlier became more skilled in learning activities. Suggestions for further research to be more in-depth both qualitatively and quantitatively explore the use of the latest technology to prepare future generations who have 21st century skills. Keywords: Parental Perspective; Computer Learning; Early childhood education References: Alkhawaldeh, M., Hyassat, M., Al-Zboon, E., & Ahmad, J. (2017). The Role of Computer Technology in Supporting Children’s Learning in Jordanian Early Years Education. Journal of Research in Childhood Education, 31(3), 419–429. https://doi.org/10.1080/02568543.2017.1319444 Ariputra. (2018). Need Assessment of Learning Inclusive Program for Students in Non-formal Early Childhood. Early Childhood Research Journal. https://doi.org/10.23917/ecrj.v1i1.6582 Atkinson, K., & Biegun, L. (2017). An Uncertain Tale: Alternative Conceptualizations of Pedagogical Leadership. Journal of Childhood Studies. Aubrey, C., & Dahl, S. (2014). The confidence and competence in information and communication technologies of practitioners, parents and young children in the Early Years Foundation Stage. Early Years, 34(1), 94–108. https://doi.org/10.1080/09575146.2013.792789 Barenthien, J., Oppermann, E., Steffensky, M., & Anders, Y. (2019). Early science education in preschools – the contribution of professional development and professional exchange in team meetings. European Early Childhood Education Research Journal. https://doi.org/DOI: 10.1080/1350293X.2019.1651937, https://doi.org/10.1080/1350293X.2019.1651937 Bredekamp, S., & Copple, C. (2009). Developmentally Appropriate Practice in Early Childhood Programs Serving Children from Birth through Age 8. Chen, R. S., & Tu, C. C. (2018). Parents’ attitudes toward the perceived usefulness of Internet-related instruction in preschools. Social Psychology of Education, 21(2), 477–495. https://doi.org/10.1007/s11218-017-9424-8 Christensen, R. (2002). Effects of technology integration education on the attitudes of teachers and students. Journal of Research on Technology in Education, 34(4), 411–433. https://doi.org/10.1080/15391523.2002.10782359 Couse, L. J., & Chen, D. W. (2010). A tablet computer for young children? Exploring its viability for early childhood education. Journal of Research on Technology in Education, 43(1), 75–98. https://doi.org/10.1080/15391523.2010.10782562 Creswell, J. W. (2012). Educational Research Planning, Conducting, and Evaluating Quantitative and Qualitative Research(4th ed.; P. A. Smith, Ed.). Boston: Pearson. Davis, J. M. (2014). environmental education and the future. (May). https://doi.org/10.1023/A Dhieni, N., Hartati, S., & Wulan, S. (2019). Evaluation of Content Curriculum in Kindergarten. Jurnal Pendidikan Usia Dini. https://doi.org/https://doi.org/10.21009/10.21009/JPUD.131.06 Dong, C., & Newman, L. (2016). Ready, steady … pause: integrating ICT into Shanghai preschools. International Journal of Early Years Education, 24(2), 224–237. https://doi.org/10.1080/09669760.2016.1144048 Dunn, J., Gray, C., Moffett, P., & Mitchell, D. (2018). ‘It’s more funner than doing work’: Children’s perspectives on using tablet computers in the early years of school. Early Child Development and Care, 188(6), 819–831. https://doi.org/10.1080/03004430.2016.1238824 Hadzigianni, M., & Margetts, K. (2014). Parents’ Beliefs and Evaluations of Young Children’s Computer Use. Australasian Journal of Early Childhood. https://doi.org/doi/pdf/10.1177/183693911403900415 Huda, M., Hehsan, A., Jasmi, K. A., Mustari, M. I., Shahrill, M., Basiron, B., & Gassama, S. K. (2017). Empowering children with adaptive technology skills: Careful engagement in the digital information age. International Electronic Journal of Elementary Education, 9(3), 693–708. Ihmeideh, F. (2010). The role of computer technology in teaching reading and writing: Preschool teachers’ beliefs and practices. Journal of Research in Childhood Education, 24(1), 60–79. https://doi.org/10.1080/02568540903439409 Jack, C., & Higgins, S. (2018). What is educational technology and how is it being used to support teaching and learning in the early years ? International Journal of Early Years Education, 0(0), 1–16. https://doi.org/10.1080/09669760.2018.1504754 Janisse, H. C., Li, X., Bhavnagri, N. P., Esposito, C., & Stanton, B. (2018). A Longitudinal Study of the Effect of Computers on the Cognitive Development of Low-Income African American Preschool Children. Early Education and Development, 29(2), 229–244. https://doi.org/10.1080/10409289.2017.1399000 Karjalainen.S., A., Pu, E. H., & Maija, A. (2019). Dialogues of Joy: Shared Moments of Joy Between Teachers and Children in Early Childhood Education Settings. International Journal of Early Childhood. https://doi.org/10.1007/s13158-019-00244-5 Kerckaert, S., Vanderlinde, R., & van Braak, J. (2015). The role of ICT in early childhood education: Scale development and research on ICT use and influencing factors. European Early Childhood Education Research Journal, 23(2), 183–199. https://doi.org/10.1080/1350293X.2015.1016804 Ko, K. (2014). The Use of Technology in Early Childhood Classrooms: An Investigation of Teachers’ Attitudes. Gaziantep University Journal of Social Sciences, 13(3), 807–819. Kong, S. C. (2018). Parents’ perceptions of e-learning in school education: implications for the partnership between schools and parents. Technology, Pedagogy and Education, 27(1), 15–31. https://doi.org/10.1080/1475939X.2017.1317659 Livingstone, S. (2012). Critical reflections on the benefits of ICT in education. Oxford Review of Education, 38(1), 9–24. https://doi.org/10.1080/03054985.2011.577938 Martin, E., R. Alvarez, Pablo, D., Haya, A., Fernández‐Gaullés, Cristina, … Quintanar, H. (2018). Impact of using interactive devices in Spanish early childhoodeducation public schools. Journal of Computer Assisted Learning. McCloskey, M., Johnson, S. L., Benz, C., Thompson, D. A., Chamberlin, B., Clark, L., & Bellows, L. L. (2018). Parent Perceptions of Mobile Device Use Among Preschool-Aged Children in Rural Head Start Centers. Journal of Nutrition Education and Behavior, 50(1), 83-89.e1. https://doi.org/10.1016/j.jneb.2017.03.006 McDaniel, B. T., & Radesky, J. S. (2018). Technoference: Parent Distraction With Technology and Associations With Child Behavior Problems. Child Development, 89(1), 100–109. https://doi.org/10.1111/cdev.12822 Nikolopoulou, K., & Gialamas, V. (2015). ICT and play in preschool: early childhood teachers’ beliefs and confidence. International Journal of Early Years Education, 23(4), 409–425. https://doi.org/10.1080/09669760.2015.1078727 Nolan, J., & McBride, M. (2014). Beyond gamification: reconceptualizing game-based learning in early childhood environments. Information Communication and Society, 17(5), 594–608. https://doi.org/10.1080/1369118X.2013.808365 Paciga, K. A., Lisy, J. G., & Teale, W. H. (2013). Better Start Before Kindergarten: computer Technology, Interactive Media and the Education of Preschoolers. Asia-Pacific Journal of Research in Early Childhood Education, 85–104. Palaiologou, I. (2016). Children under five and digital technologies: implications for early years pedagogy. European Early Childhood Education Research Journal, 24(1), 5–24. https://doi.org/10.1080/1350293X.2014.929876 Plowman, L. (2015). Researching young children’s everyday uses of technology in the family home. Interacting with Computers, 27(1), 36–46. https://doi.org/10.1093/iwc/iwu031 Plowman, L., & McPake, J. (2013). Seven Myths About Young Children and Technology. Childhood Education, 89(1), 27–33. https://doi.org/10.1080/00094056.2013.757490 Sageide, B. M. (2016). Norwegian early childhood teachers’ stated use of subject-related activities with children, and their focus on science, technology, environmental issues and sustainability. International Journal of Primary, Elementary and Early Years Education. https://doi.org/11250/2435060/955-11623-1-PB Tate, T. P., Warschauer, M., & Kim, Y. S. G. (2019). Learning to compose digitally: the effect of prior computer use and keyboard activity on NAEP writing. Reading and Writing, 32(8), 2059–2082. https://doi.org/10.1007/s11145-019-09940-z Theodotou, E. (2010). Using Computers in Early Years Education: What Are the Effects on Children’s Development? Some Suggestions Concerning Beneficial Computer Practice. Online Submission, (December). UNESCO. Rethinking Education. Towards a global common good. , (2015). Vartuli, S., Bolz, C., & Wilson, C. (2014). A Learning Combination: Coaching with CLASS and the Project Approach. Early Childhood Research & Practice Journal, 1–16. Vittrup, B., Snider, S., Rose, K. K., & Rippy, J. (2016). Parental perceptions of the role of media and technology in their young children’s lives. Journal of Early Childhood Research, 14(1), 43–54. https://doi.org/10.1177/1476718X14523749 Waal, E. D. (2019). Fundamental Movement Skills and Academic Performance of 5- to 6-Year-Old Preschoolers. Early Childhood Education Journal, 455–456. https://doi.org///doi.org/10.1007/s10643-019-00936-6 Wang, Q. (2008). A generic model for guiding the integration of ICT into teaching and learning. Innovations in Education and Teaching International, 45(4), 411–419. https://doi.org/10.1080/14703290802377307 Wolfe, S., & Flewitt, R. (2010). New technologies, new multimodal literacy practices and young children’s metacognitive development. Cambridge Journal of Education, 40(4), 387–399. https://doi.org/10.1080/0305764X.2010.526589 YurtaNılgün, Ö., & Kalburan, C. (2011). Early childhood teachers’ thoughts and practices about the use of computers in early childhood education. Early Childhood Educaiton: Yesterday, Today, and Tomorrow. Yusmawati, & Lubis, J. (2019). The Implementation of Curriculum by Using Motion Pattern. Jurnal Pendidikan Usia Dini. https://doi.org/DOI:https://doi.org/10.21009/10.21009/JPUD.131.14